THE EFFECTIVENESS OF PASTORAL COUNSELING SERVICES FOR YOUNG PEOPLE ADDICTED TO GADGET - Meldianto (Prodi Bimbingan Konseling Universitas Negeri Manado, 2023)
Gadgets are communication technology devices. Gadget wars now make people's lives easier and more comfortable and bring changes in mindsets and even touch the ground of human character and attitudes. The impact of excessive use of gadgets is bad for the attitude of the younger generation in life. The impact is that it results in bad behavior that interferes with learning, interferes with the health and attitudes of the younger generation and causes excessive spending. So it takes direction and limits from parents for children to use gadgets. To overcome gadget addiction can be done psychologically and non-psychologically. Non-psychological actions can be done through pastoral counseling to addicts. Here the congregation is trained to be able to testify (not just fellowship) about God's work in his life. The pastoral witness is the answer to human needs regarding warmth, care and support, so pastoral care is aimed at the ability of the congregation to preach the gospel which is basically the priesthood of all believers. The results of the study found that preventing the bad influence of technology on youth, it has been explained that the most important thing is to invite young people to see technology based on God's Word then guide them and teach them to be responsible for the use of technology through pastoral counseling